Optimal Urban Water Allocation Strategies Under Inter-Basin Water Transfer: Case of Nairobi City, Kenya - R. W.; Mwangi, J. K.; Mwangi, J. K.; Karimi, P.; Kiptala, J. K. (African Journal of Education,Science and Technology (AJEST), 2023)
Most urban cities in the world are facing water insecurity as a result of rising water demand while the supply remains uncertain due to climate variability. To curb the growing water demand, most cities in the world have invested in inter-basin water transfers (IBWTs). IBWTs have the ability to balance both the temporal and spatial distribution of water resources. To enhance their reliability, IBWTs are integrated with water storage facilities like reservoirs. The study evaluated optimal water allocation strategies with IBWT for Nairobi City. First, Sentinel imagery using normalized difference water index (NDWI), as a proof of concept, was used to investigate changes in reservoir levels of Thika dam due to IBWT.Water Evaluation and Planning System (WEAP) model was used to evaluate water allocation strategies with the new IBWT project (Northern Collector Tunnel Phase 1 (NCT 1)) and planned water sources up to year 2035. NDWI was able to detect changes in reservoir area due to the increased water flows from NCT I to Thika Reservoir. However, the increased flows from NCT I would not meet the city’s water demands in the very dry, dry and normal years which had a supply coverage of 31%, 35% and 47% respectively. While the government’s objective is to increase the supply coverage in Nairobi City to over 70%, this will only be achievable in the wet and very wet years as the coverage increased to 71% and 92% respectively. From the results, even with demand management measures, NCT 1 will still not meet the desired supply coverage in the very dry, dry and normal years. However, additional water sources together with demand management measures provides opportunities of alleviating water shortages by achieving the desired supply coverage under all climatic conditions. Further, the current and future water sources plans are surface water storage which are heavily affect by rainfall variability. Thus, the national and the Nairobi County governments, need to come up with an integrated water resources management systems where water resources development is integrated with water demand management. Such may include supplementing centralized storage systems with decentralized ones such as rainwater harvesting, sustainable groundwater use and waste water reuses in order to enhance urban water security for Nairobi residents.